Large herbivores that strive mightily but eat and drink as friends - de Boer, W F; Prins, H H T (Oecologia, 1990)
Grazing in patches of Cynodon dactylon and of Sporobolus spicatus by four large herbivores, and the interaction between these sedentary herbivores was studied in Lake Manyara National Park, northern Tanzania. The herbivores were the African buffalo, Syncerus caffer; the African elephan, Loxodonta africana; the Burchell's zebra, Equus burchelli; and the wildebeest, Connochaetus taurinus. Four different hypotheses of the interactions between the herbivores were tested, viz., increased predator detection/protection through association of species, facilitation of the food intake through the influence of other species, use by other species of the food manipulation strategy of buffalo, and interspecific competition for food. On the level of a single day, zebra and wildebeest were symbiotic, which could have been caused by an increased chance of predator detection. A similar association between buffalo and wildebeest or zebra was also detected on C. dactylon grasslands. There was no indication of facilitation between any of the herbivores. Buffalo had a despotic relationship with elephant, that is the elephant's consumption was lowered when buffalo had visited a patch prior to their arrival. When elephant and buffalo arrived at the same time there appeared to be scramble competition between them.Habitat overlap was calculated for four pairs of species. In conjunction with the analyses of the patch visits, it was concluded that a small overlap was associated with interspecific competition and a large habitat overlap was associated with symbiosis.